Credit card interchange fees - Rochet, Jean-Charles; Wright, Julian (Journal of Banking & Finance, 2010)
We build a model of credit card pricing that explicitly takes into account credit functionality. In the model a monopoly card network always selects an interchange fee that exceeds the level that maximizes consumer surplus. If regulators only care about consumer surplus, a conservative regulatory approach is to cap interchange fees based on retailers’ net avoided costs from not having to provide credit themselves. This always raises consumer surplus compared to the unregulated outcome, sometimes to the point of maximizing consumer surplus.